2012
DOI: 10.1007/s00249-012-0828-2
|View full text |Cite
|
Sign up to set email alerts
|

Probing the catalytic allosteric mechanism of rabbit muscle pyruvate kinase by tryptophan fluorescence quenching

Abstract: Pyruvate kinase acts as an allosteric enzyme, playing a crucial role in the catalysis of the final step of the glycolytic pathway. In this study, site-specific mutagenesis and tryptophan fluorescence quenching were used to probe the catalytic allosteric mechanism of rabbit muscle pyruvate kinase. Movement of the B domain was found to be essential for the catalytic reaction. Rotation of the B domain in the opening of the cleft between domains B and A induced by the binding of activating cations allows substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…S99 and K137 of PKM were located in the A and B domains, respectively. Li et al reported that changes in the B domain were more sensitive and important for PKM glycolytic activity because of its high flexibility . In this study, PKM_K137Q showed a lower glycolytic activity compared with the other four PKM variants (Figure A).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…S99 and K137 of PKM were located in the A and B domains, respectively. Li et al reported that changes in the B domain were more sensitive and important for PKM glycolytic activity because of its high flexibility . In this study, PKM_K137Q showed a lower glycolytic activity compared with the other four PKM variants (Figure A).…”
Section: Discussionmentioning
confidence: 52%
“…Li et al reported that changes in the B domain were more sensitive and important for PKM glycolytic activity because of its high flexibility. 30 In this study, PKM_K137Q showed a lower glycolytic activity compared with the other four PKM variants (Figure 2A). The results of molecular docking suggested that the binding of PKM_K137Q and PEP decreased, which might be a main reason for the low glycolytic activity of PKM_K137Q rather than the binding of PKM_K137Q and ADP.…”
Section: ■ Discussionmentioning
confidence: 52%
“…The domain has been documented to be highly mobile, a characteristic that underpins its expected function within catalysis and regulation. It is proposed that after metal cations coordinate in the active site, the lid domain rotates to allow substrate binding, after which it moves to cover and dehydrate the active site cleft (Li et al 2012;Naithani et al 2015). The position and amount of movement seen in the lid is known to vary depending upon substrate binding within the active site and whether fructose-1,6-phosphate is bound at the regulatory domain (Li et al 2012;Valentini et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that after metal cations coordinate in the active site, the lid domain rotates to allow substrate binding, after which it moves to cover and dehydrate the active site cleft (Li et al 2012;Naithani et al 2015). The position and amount of movement seen in the lid is known to vary depending upon substrate binding within the active site and whether fructose-1,6-phosphate is bound at the regulatory domain (Li et al 2012;Valentini et al 2000). However, experiments that have provided these insights are generally focused on catalysis (Oria-Hernández et al 2005), regulation (Valentini et al 2000), or deficiencies in human pyruvate kinase mutants (Valentini et al 2002;van Wijk et al 2009), and only involve site directed mutagenesis studies.…”
Section: Introductionmentioning
confidence: 99%